IoT based Smart Aquaculture Monitoring System for Fish Tank Management - P, Arthi; N, Mahesh; H, Saipurusoth; B, Janardhanam (Journal of Ubiquitous Computing and Communication Technologies, 2024)
Aquaculture, the farming of aquatic organisms, plays a critical role in meeting the increasing global demand for seafood. Effective monitoring and management of aquaculture systems are essential for ensuring optimal conditions and maximizing productivity. This research presents a comprehensive aquaculture-based fish tank monitoring system designed to enhance operational efficiency and fish welfare. At the heart of the system is the Arduino Uno microcontroller, serving as the central processing unit to coordinate various functions. Key components include pH sensor for continuous monitoring of acidity levels, turbidity sensor for detecting suspended particles, and water level sensor for maintaining optical water levels within the tank. In the event of abnormal pH levels or high turbidity, the system triggers automated alerts, sending notifications to the designated owner through SMS and transmitting data to an IoT website for remote monitoring. To ensure consistent environmental conditions, two pump motors are utilized: one for automatic water replenishment in case of water level fluctuations and another for removing water in case of particle accumulation. Furthermore, the system integrates a servo motor mechanism for precise dispensing of fish feed at predetermined intervals, promoting healthy growth and nutrition. Control over pump motors and feeding schedules is facilitated through a user-friendly website interface, providing operators with seamless management capabilities.